Persistence : all ways butch and femme - Coyote, Ivan E.; Sharman, Zena (Arsenal Pulp Press, 2011)
Persistence is a raucous, insightful, sexy, and sometimes dangerous look at what the words butch and femme can mean in today's ever-shifting gender landscape, with one eye on the past and the other on what is to come.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; fem1000; identités; identités LGBTQIA2+; lesbianisme; littérature; premier cycle; périodes historiques; queer; régions géographiques; thématiques; études littéraires